Perancangan Aplikasi sebagai Media Pemahaman Notasi Musik bagi Anak Usia Dini - Fazrin Sheila Ananda; Yudi Sukmayadi; Lanang Riyadi (Program Studi Pendidikan Musik FBS UNP, 2024)
Purpose: This research aims to develop a music learning application specifically designed for early childhood, utilizing smartphone technology in an educational context. The need for innovative and engaging learning methods is becoming increasingly important, especially since the COVID-19 pandemic has driven digital transformation in education. Methods: This research uses the Research and Development (R&D) method with a Design and Development Research approach. The main focus is on developing an app that educates children about the basics of music, including music notation, pulse, tempo, and note values. The app is designed to make it easier for teachers to deliver music learning materials and provide parents with educational tools to teach music to children at home. Results and Discussion: In its development, this application uses visual and audio elements, such as bright colors, images, voice over narration, and animation, to attract and maintain children's focus. Considering the limitations of teachers in using learning media and the prevalence of gadget use by children, this application is expected to be a more interactive and fun learning resource. Conclusion: This research contributes to the development of music learning media in early childhood and kindergarten schools, as well as being an alternative educational resource for parents in educating their children about music at home, particularly through the positive and educational use of gadgets.